Investigating the Effect of Social Support, Healthy Behavior, and Religious Coping on Free COVID-19 Pandemic through Immunity in West Sumatera, Indonesia - Isramilda, Isramilda; Lebrata, Lebrata; Indrayani, Indrayani; Satriawan, Bambang (International Journal of Industrial Engineering, Technology & Operations Management, 2023)
The coronaviruses are a large family of viruses that cause disease in humans and animals. Data from West Sumatra captures that until December 31, 2020, there were 23,441 confirmed cases of COVID-19 and 21,601 people recovered. Does the recovery from COVID-19 have anything to do with social support, health behaviors that are always recommended by Regional Leaders in West Sumatra, Religious coping for the people of West Sumatra which affects the free pandemic of COVID-19? To answer this phenomenon, it is necessary to investigate the effect of social support, healthy behavior, religious coping on COVID-19 Pandemic free through immunity in West Sumatra, Indonesia.as a population, with the Slovin formula sample Becomes 174 respondents. The recovery of COVID-19, whether it has to do with social support, religious coping in which West Sumatra, and health behaviors that are always recommended by the Regional Leadership in the West Sumatera, give rise to immunity so that it influences the pandemic COVID-19. The research model used is a mixed-method, by combining quantitative with SEM software AMOS-24 and qualitative with interviews with respondents and the community as well as the COVID-19 West Sumatera Cluster Team. The result indicates that changes in immunity are influenced by religious coping, healthy behavior and social support is 95.60%, the remaining 3.40% is influenced by other variables not included in this study. changes in the Free COVID-19 pandemics are influenced by 100% religious coping, healthy behavior, social support and immunity.